Design of Experimental Problem Solving-Based Learning Program to Improve Mental Model and to Enhance Mental-Modeling Ability - Supriyatman, S.; Suhandi, A.; Rusdiana, D.; Samsudin, A.; Wibowo, F. C.; Mansyur, J. (Department of Physics, Faculty of Mathematics and Natural Sciences, 2018)
Research on developing experimental problem solving-based learning program to overcome the low mental model (MM) and mental-modeling abilities (MMA) physics teacher candidate in one of the college teachers in Palu have been conducted. Mental model construction is the Ã¢â‚¬Å“coreÃ¢â‚¬Â of meaningful learning and along with MMA (modeling) become a keyword to understand the key concepts in the science learning. The development of this learning program was using R & D method. Development process from requirement analysis phase until implementation process has already been described using 4D model: define, design, develop and disseminate. The subject matter of this research was the Basic Physics II course on the topic of electricity and magnetism. Based on the data analysis and findings at each stage of development, it is concluded that the learning program stages which have improved MM and also enhanced the MMA of physics teacher candidates consist of learning orientation phase; orientation to the problem; pre-experimental brainstorming; experiment; evaluation; as well as the phase of reinforcement and follow-up.Penelitian tentang pengembangan program berbasis eksperimen problem solving untuk mengatasi rendahnya mental model (MM) dan mental-modeling abilities (MMA) calon guru fisika di salah satu guru perguruan tinggi di Palu telah dilakukan. Konstruksi model mental adalah inti dari pembelajaran yang bermakna dan bersama dengan MMA (pemodelan) menjadi kata kunci untuk memahami konsep-konsep kunci dalam sains. Pengembangan program pembelajaran ini menggunakan metode R & D. Proses pengembangan dari tahap analisis kebutuhan hingga proses implementasi dijelaskan menggunakan model 4D: define, design, develop, disseminate. Materi yang dikaji dalam penelitian ini adalah mata kuliah fisika dasar 2 tentang topik listrik dan magnet. Berdasarkan analisis data dan temuan pada setiap tahap perkembangan, disimpulkan bahwa tahapan program pembelajaran yang telah memperbaiki MM dan juga meningkatkan MMA calon guru fisika terdiri dari fase orientasi pembelajaran; orientasi pada masalah; pra-brainstorming eksperimental; percobaan; evaluasi; serta fase penguatan dan tindak lanjut.